Application of Arduino-based Control System Hydraulic Barricades to Improve Safety at Level Crossing Safety - Mulyani, Haniva; Abdurahim, Muhammad Nabil; Maulana, Muhammad Ilham Wisnu; Rafsanjani, Attariq; Rohman, Fatchur; Arrifda, Melin (LifeSciFi, 2025)
Level crossings in Indonesia, particularly unguarded ones, experience frequent accidents, necessitating innovative safety solutions. This study aims to develop a servo-driven barricade system using an Arduino Uno microcontroller and infrared sensors to enhance safety at level crossings by preventing vehicle crossings during train passages. The research was conducted through a structured process involving both online coordination via communication platforms and offline activities at the Faculty of Transportation and Logistics Engineering, Institute of Transportation and Logistics Trisakti, and a vendor in Ciputat from April to August 2024. The methodology encompassed problem identification, conceptualization, system design with a 1:50 scale miniature, prototyping of a 1:10 scale iron barricade, testing in controlled environments, and evaluation of sensor and servo motor performance. Findings indicate that the system consistently detected train arrivals with 100% sensor accuracy and actuated barricades within 2 seconds, effectively blocking traffic in simulations and miniature tests. This research concludes that the servo-driven barricade system offers significant potential to improve safety at level crossings, with recommendations for field trials to assess environmental resilience and integration with Internet of Things technology for real-time monitoring to enhance scalability and effectiveness.